Congress of Neurological Surgeons Systematic Review and Evidence-Based Guideline on Surgical Techniques and Technologies for the Management of Patients With Nonfunctioning Pituitary Adenomas. Issue 4 (October 2016) - Kuo, John S.; Barkhoudarian, Garni; Farrell, Christopher J.; Bodach, Mary E.; Tumialan, Luis M.; Oyesiku, Nelson M.; Litvack, Zachary; Zada, Gabriel; Patil, Chirag G.; Aghi, Manish K.
Abstract : BACKGROUND: Numerous technological adjuncts are used during transsphenoidal surgery for nonfunctioning pituitary adenomas (NFPAs), including endoscopy, neuronavigation, intraoperative magnetic resonance imaging (MRI), cerebrospinal fluid (CSF) diversion, and dural closure techniques. OBJECTIVE: To generate evidence-based guidelines for the use of NFPA surgical techniques and technologies. METHODS: An extensive literature search spanning January 1, 1966, to October 1, 2014, was performed, and only articles pertaining to technological adjuncts for NFPA resection were included. The clinical assessment evidence-based classification was used to ascertain the class of evidence. RESULTS: Fifty-six studies met the inclusion criteria, and evidence-based guidelines were formulated on the use of endoscopy, neuronavigation, intraoperative MRI, CSF diversion, and dural closure techniques. CONCLUSION: Both endoscopic and microscopic transsphenoidal approaches are recommended for symptom relief in patients with NFPAs, with the extent of tumor resection improved by adequate bony exposure and endoscopic visualization. In select cases, combined transcranial and transsphenoidal approaches are recommended. Although intraoperative MRI can improve gross total resection, its use is associated with an increased false-positive rate and is thus not recommended. There is insufficient evidence to recommend the use of neuronavigation, CSF diversion, intrathecal injection, or specific dural closure techniques. The full guidelines document for this chapter can be located athttps://www.cns.org/guidelines/guidelines-management-patients-non-functioning-pituitary-adenomas/Chapter_6 . ABBREVIATIONS: CSF, cerebrospinal fluid NFPA, nonfunctioning pituitary adenoma